Choline Kinase alpha Expression during RA-induced Neuronal Differentiation: role of C/EBPβ - Domizi, Pablo Daniel (2014)
Neuronal differentiation is a complex process characterized by a halt in proliferation and extension of neurites from the cell body. This process is accompanied by changes in gene expression that mediate the redirection leading to neurite formation and function. Acceleration of membrane phospholipids synthesis is associated with neurite elongation, and phosphatidylcholine (PtdCho) is the major membrane phospholipid in mammalian cells. The transcription of two genes in particular encoding key enzymes in the CDP–choline pathway for PtdCho biosynthesis are stimulated; the Chka gene for choline kinase (CK) alpha isoform and the Pcyt1a gene for the CTP: phosphocholine cytidylyltransferase (CCT) alpha isoform. We report that the stimulation of CKα expression during retinoic acid (RA) induced differentiation depends on a promoter region that contains two CCAAT/Enhancerbinding Protein-β (C/EBPβ) sites. We demonstrate that during neuronal differentiation of Neuro-2a cells, RA induces Chka expression by a mechanism that involves ERK½ activation which triggers C/EBPβ expression. Elevated levels of C/EBPβ bind to the Chka proximal promoter (Box1) inducing CKα expression. In addition we identified a downstream sequence named Box2 which together with Box1 is required for the promoter to reach the full induction. This is the first elucidation of the mechanism by which the expression of Chka is coordinately regulated during neuronal differentiation.